Productivity of soybean (Glycille max) genotypes as influenced by nitrogen and sulphur niutrition* - VYAS, A K; BILLORE, S D; JOSHI, O P; PACHLA, N (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted for 3 years to study the effect of balanced and continuous supply of nitrogen and suphur on productivity and energy budgeting of soybean genotypes. Results revealed that significantly higher seed yield was recorded with' JS 335' to the extent of 29.9 and 30.6% over' PK 416' and'Ahilya 4', resepectively. Additional application of20 kg nitrogen at 60 days after sowing increased the seed yield by 11.1% over recommended dose offertilizer nitrogen (20 kg/ha as basal). Basal application of sulphur @ 40 kg/ha increased the yield by 21.8% over basal application ofnitrogen @20 kg/ha. Application of20 kg nitrogen +40 kg sulphur/ha as basal produced the maximum seed yield. Energy analyses showed that the' JS 335' and application of N20S4 0 was found most energy productivity and energy efficient than rest of the genotypes. ' JS 335' and additional application of 20 kg/ha nitrogen at 60 days after sowing resulted in highest protein and lowest oil content.